2010 International Conference on User Science and Engineering (I-USEr) 2010
DOI: 10.1109/iuser.2010.5716747
|View full text |Cite
|
Sign up to set email alerts
|

Hearing but not listening: Auditory icons and presence

Abstract: This paper explores the usage of auditory icons in creating the feeling of presence of a remote person in a virtual simulation of domestic life. Auditory icons are the representation of processes or activities using everyday sounds. Presence is defined in this research as 'the feeling of being with others'. In this research, domestic life is simulated using the game called The Sims. Participants were asked to play the game while being able to hear auditory icons that represent another player who were playing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The factors of 'the spatial characteristics of sound' [14], 'spatialized sound' [43], 'spatialized sound source' [44], and binary audio (spatial acoustics) [45] were grouped into 'implementing the spatial properties of sound' because they use the common concept of 'space' according to P1's opinion. 'Similarity to real-world sounds [34], 'realization of real sounds' [39], 'reproduction of soundscapes' [40], and 'everyday soundscapes' [41] were grouped as 'implementing realistic soundscapes in a metaverse environment' because they use the common auditory concept of 'real soundscapes' according to P1's opinion. 'Perceived location factor of sound' [22], threedimensional spatial representation of sound [39], and 'three-dimensional representation of sound' [42] were grouped into 'three-dimensional perception of sound' because they use the common concept of 'location' according to P2's opinion.…”
Section: Results Of Grouping For Auditory Evaluation Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The factors of 'the spatial characteristics of sound' [14], 'spatialized sound' [43], 'spatialized sound source' [44], and binary audio (spatial acoustics) [45] were grouped into 'implementing the spatial properties of sound' because they use the common concept of 'space' according to P1's opinion. 'Similarity to real-world sounds [34], 'realization of real sounds' [39], 'reproduction of soundscapes' [40], and 'everyday soundscapes' [41] were grouped as 'implementing realistic soundscapes in a metaverse environment' because they use the common auditory concept of 'real soundscapes' according to P1's opinion. 'Perceived location factor of sound' [22], threedimensional spatial representation of sound [39], and 'three-dimensional representation of sound' [42] were grouped into 'three-dimensional perception of sound' because they use the common concept of 'location' according to P2's opinion.…”
Section: Results Of Grouping For Auditory Evaluation Factorsmentioning
confidence: 99%
“…Based on these results, it was identified that five main components, including 'realistic auditory background' and 'acoustic aesthetics', explained more than 70% of the variance in auditory presence in metaverse environments. While previous studies have mainly focused on the spatial characteristics of auditory presence in metaverse environments or the congruence of auditory and visual atmospheres [36][37][38][39][40][41][42], the study focuses on the importance of AUX and its impact on presence. As expected from the above research questions, it was confirmed that auditory presence and AUX factors can enhance presence when they act complementarily.…”
Section: Results Of the Survey And Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations